Kanamycin sensitivity of cultured tissues of Piper nigrum L. - VELUTHAMBI, B SASIKUMAR, K (Journal of Spices and Aromatic Crops, 2017)
The kanamycin sensitivity for callus growth was studied in vitro in a cultivar of black pepper (Piper nigrum) using cotyledons as explants to investigate the suitability of kanamycin resistance as a selectable marker for Agrobacterium mediated transformation. Callus formation was completely inhibited at 50 ug ml-1 and above concentrations of kanamycin suggesting that 50 ug ml-1 is the minimum concentration needed to select the transformed tissues.